A Study on the Failure Mechanism of a Phase-Change Memory in Write/Erase Cycling - Lee, Suyoun; Jeong, Jeung-hyun; Lee, Taek Sung; Kim, Won Mok; Cheong, Byung-ki (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2009)
Using a phase-change memory (PCM) device composed of Ge2Sb2Te5 (GST), We studied the mechanism of the SET-stuck failure (SSF), a constantly low-resistance state during write/erase (W/E) cycling. The SSF state was characterized with increased RESET current and decreased threshold voltage, which were thought to be due to depletion of Ge and enrichment of Sb inside the active volume of GST. Moreover, we found that device characteristics of an SSF-PCM could be recovered by reversing bias polarity and the repaired device could endure many WE cycles, implying that field-induced ion migration was the major cause of the SSF of a PCM.